Pengaruh Lingkungan Kerja Terhadap Kinerja Pegawai Pada Kantor Badan Perencanaan Pembangunan Daerah Kabupaten Batang Hari - Budi Darma; Azwar Anas (Universitas Batanghari Jambi, 2019)
This study entitled the influence of the work environment on employee performance at the Office of the Regional Development Planning Board of Batang Hari Regency. In this study will be tested how much influence the work environment on employee performance. In analyzing data, in this study using Path Analysis and t test. This study has the same population and sample of 63 people. Data retrieval is done by distributing question questionnaires. Based on the discussion it can be concluded that the influence of the work environment on performance is 34.45%. And the Work Environment has a partial and significant effect on employee performance at the Office of the Regional Development Planning Board of Batang Hari Regency.